Pengembangan Kurikulum Pendidikan Islam dalam Menghadapi Tantangan di Era Digital - Restu Alfaris; Putri Alayda Nabilla; Siti Aisyah Gunawan; Riska Silviana Azzahra; Sri Yanti; Achmad Junaedi Sitika (STID Raudlatul Iman Sumenep, 2026)
The rapid development of digital technology has significantly transformed various aspects of human life, including education. This condition requires Islamic education to adapt by developing a curriculum capable of addressing contemporary challenges while maintaining the fundamental values of Islamic teachings. This study aims to analyze the challenges faced by Islamic education in the digital era and examine relevant curriculum development strategies to respond to these changes. The study employed a qualitative approach using a library research method. Data were collected from books, scientific journals, articles, and other relevant literature discussing Islamic education curriculum development in the digital era. Data analysis was conducted descriptively through the processes of data collection, reduction, presentation, and conclusion drawing. The findings indicate that the main challenges of Islamic education in the digital era include the rapid flow of information, low digital literacy, changes in students' learning patterns, and the need to improve teachers’ competencies. Curriculum development should focus on integrating technology into learning, strengthening character education, enhancing digital literacy, and improving educators’ competencies. Therefore, the Islamic education curriculum is expected to produce generations who are faithful, possess noble character, adapt to technological advancements, and are prepared to face global challenges. Perkembangan teknologi digital telah membawa perubahan yang signifikan dalam berbagai aspek kehidupan, termasuk bidang pendidikan. Kondisi ini menuntut pendidikan Islam untuk melakukan adaptasi melalui pengembangan kurikulum yang mampu menjawab tantangan zaman tanpa meninggalkan nilai-nilai dasar ajaran Islam. Penelitian ini bertujuan untuk menganalisis tantangan yang dihadapi pendidikan Islam di era digital serta mengkaji strategi pengembangan kurikulum yang relevan dalam menghadapi perubahan tersebut. Penelitian menggunakan metode studi kepustakaan (library research) dengan pendekatan kualitatif. Data diperoleh melalui kajian berbagai buku, jurnal ilmiah, artikel, dan sumber literatur yang berkaitan dengan pengembangan kurikulum pendidikan Islam di era digital. Analisis data dilakukan secara deskriptif-kualitatif melalui proses pengumpulan, reduksi, penyajian, dan penarikan kesimpulan. Hasil kajian menunjukkan bahwa tantangan utama pendidikan Islam di era digital meliputi derasnya arus informasi, rendahnya literasi digital, perubahan pola belajar peserta didik, serta tuntutan peningkatan kompetensi guru. Pengembangan kurikulum pendidikan Islam perlu dilakukan melalui integrasi teknologi dalam pembelajaran, penguatan pendidikan karakter, peningkatan literasi digital, serta pengembangan kompetensi pendidik. Dengan demikian, kurikulum pendidikan Islam diharapkan mampu menghasilkan generasi yang beriman, berakhlak mulia, adaptif terhadap perkembangan teknologi, dan siap menghadapi tantangan global.